GAMBARAN PERILAKU IBU DALAM PENYEDIAAN SAYUR KELUARGA DI KELURAHAN PASIR BIDANG KECAMATAN SARUDIK KABUPATEN TAPANULI TENGAH TAHUN 2012 - Airin Nurul Hasanah (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
Vegetable is a food that has a very big roles for the body as a source of vitamins, minerals and food fiber, even though the body only needs in small quantities but it has an important function as aregulator and a protective agent. The purpose of research is to reveal how the mother's behavior supply vegetables for family consumption in Pasir Bidang vilage of Sarudik at Central Tapanuli district. This type of research is descriptive with cross sectional method. Total population of the study is 872 households and the sample are 63 mothers. These results indicate that the  knowledge level of the respondents about the vegetables are in middle category that is about 31 people (49,2%), the attitude of respondents in the middle category as many as 57 people (90,5%), the action of respondents in the middle category too and there are about 60 people (95,2%). For tabulation of attitudes based on knowledge obtained that for knowledgeable respondents were on average also have a stance in  were as many as 29 people (93,5%), to tabulate action based on the knowledge gained that on average respondents were knowledgeable own actions in the category were also as many as 30 people (96.8%), while for the action based attitudes showed that on average the respondents whose attitude is at middle category  was also has an action in the medium category too and there are as many as 55 people (96,5%).